Formation of TPACK and Acmeological Competency of Future Teachers in Foreign Language Education - Joldanova, D.; Tleuzhanova, G.; Kitibayeva, A.; Smanova, G.; Mirza, N. (International Journal of Education in Mathematics, Science and Technology, 2022)
The aim of this study is to determine the effects of acmeological-based teaching activities in foreign language lessons on learners' foreign language self-efficacy, foreign language learning motivation and Technological Pedagogical Content Knowledge (TPACK) skills. The research was carried out in the Faculty of Foreign Languages, Department of the Theory and Practice of Foreign Languages Training of a university in Kazakhstan in the 2021-2022 academic year. The study, which was conducted with 35 students in the experimental and 35 control groups for 6 weeks, was designed according to the experimental model with the control group, which is one of the quantitative research methods. Foreign language learning self-efficacy scale, foreign language learning motivation scale and TPACK skill test were used as data collection tools in the study. According to the findings of the study, it was determined that there was a significant difference in favor of the experimental group in the post-test scores (foreign language learning self-efficacy, foreign language learning motivation and TPACK skill test scores) of the experimental group, in which activities based on the acmeological approach, and the control group, in which traditional teaching was applied.
Keywords: Acmeological approach; Self-efficacy; Foreign language learning; Motivation; TPACK; Experimental research